High-power socket needle core terminal and barrel plating process thereof

By pre-treating, pre-plating, and main plating processes for high-power socket pin core terminals, combined with modified nano-silicon carbide particles, the problems of insufficient coating adhesion, poor wear resistance, and weak corrosion resistance in existing technologies have been solved. This has achieved uniformity and stability of the coating, extended the service life of the terminals, and reduced production costs.

CN120967466APending Publication Date: 2025-11-18WANMING ELECTROPLATING INTELLIGENT TECH (DONGGUAN) CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511111788.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-08-08
Publication Date
2025-11-18

AI Technical Summary

Technical Problem

Existing high-power socket pin terminals suffer from problems such as insufficient conductivity, heat accumulation, poor contact, oxidation, and corrosion during use, leading to performance degradation and shortened service life. Furthermore, the barrel plating process struggles to achieve uniform plating thickness and sufficient adhesion.

Method used

The process involves pretreatment, pre-plating, and main plating, including degreasing, pickling, micro-etching and roughening, precise preparation of pre-plating solution and main plating solution, combined with the use of modified nano-silicon carbide particles, as well as passivation and sealing treatment, to form a uniform and dense coating, thereby improving the coating's adhesion, wear resistance and corrosion resistance.

Benefits of technology

It significantly improves the adhesion, wear resistance, and corrosion resistance of the coating, extends the service life of the terminals, reduces production costs, meets environmental protection requirements, and improves production efficiency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005540076950000141
    Figure BDA0005540076950000141
Patent Text Reader

Abstract

The invention relates to the technical field of metal surface treatment, and particularly discloses a barrel plating process of a high-power socket needle core terminal, which comprises the following steps: firstly, carrying out oil removal, acid pickling and micro-etching roughening pretreatment on the needle core terminal to clean the surface and enhance the binding force of a plating layer; then sequentially carrying out barrel plating in a pre-plating solution containing main salt, a complexing agent, conductive salt and a surfactant and a main plating solution containing main salt, an organic amine complexing agent, a buffering agent, a leveling agent, a brightening agent and modified nano silicon carbide particles; and finally, carrying out post-plating treatment including passivation treatment and sealing treatment to obtain the product. According to the barrel plating process, the wear resistance and corrosion resistance of the plating layer of the high-power socket needle core terminal and the adhesive force of the plating layer and the base material are improved, and the service life of the needle core terminal is effectively prolonged.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of metal surface treatment technology, and in particular to a high-power socket pin core terminal and its barrel plating process. Background Technology

[0002] In the operation of modern electrical equipment, high-power socket pin terminals play a crucial connection role. However, existing high-power socket pin terminals have revealed numerous problems in practical use, seriously affecting their performance and reliability. As the power of electrical equipment continues to increase, the requirements for the conductivity of socket pin terminals are also rising. However, most high-power socket pin terminals use ordinary metal materials with high resistivity. When a large current passes through, a large amount of heat is generated. Furthermore, existing plating processes have failed to effectively improve heat dissipation; some poor plating even increases contact resistance, leading to even more heat generation. This heat accumulation not only wastes electrical energy but also causes the terminal temperature to rise continuously, accelerating material aging, deteriorating conductivity, and in severe cases, potentially causing electrical fires and other safety accidents.

[0003] Secondly, frequent contact failures occur for several reasons. Firstly, prolonged insertion / extraction forces and equipment vibration alter the microstructure of the terminal surface, increasing contact resistance. If the plating process cannot provide sufficient wear resistance and cushioning, it accelerates these microstructural changes, leading to wear during insertion / extraction and making the terminal surface more prone to deformation, further increasing contact resistance. Secondly, in industrial or high-frequency applications, oxide films easily form on the terminal surface, hindering current conduction. Existing plating processes fail to provide reliable oxidation protection; some plating layers even exhibit weak adhesion, allowing micro-gaps to develop under environmental conditions, enabling oxygen and moisture to penetrate and accelerating oxidation. This results in frequent contact failures, affecting the stable operation of electrical equipment.

[0004] In humid environments or environments containing corrosive gases or chemicals, the pin terminals of existing high-power sockets are susceptible to corrosion. This is closely related to the plating process, as ordinary plating processes cannot provide durable and effective protection. On the one hand, the plating thickness is uneven, with thin areas unable to block corrosive media; on the other hand, the adhesion between the plating and the substrate is weak, making the plating prone to peeling off under the action of corrosive media. This exposes the terminals directly to the corrosive environment, severely impairing their conductivity and mechanical properties and significantly shortening their service life.

[0005] The aforementioned problems are intertwined, resulting in a short lifespan for the pin terminals of existing high-power sockets. Frequent replacements not only increase costs but also severely affect the continuity and stability of electrical equipment operation, causing numerous inconveniences to production and daily life.

[0006] Furthermore, existing barrel plating processes have several significant drawbacks when applied to high-power socket pin terminals. Insufficient control over plating thickness uniformity leads to substantial differences in thickness across different areas of the terminal surface. In critical areas, such as areas of concentrated current or prone to wear, an excessively thin plating layer fails to provide adequate protection, while an excessively thick layer in other areas results in material waste. Simultaneously, the adhesion between the plating layer and the substrate is weak, making it prone to peeling during use, especially under impact or temperature changes. Once peeled, the terminal loses protection and is directly exposed to various adverse factors, accelerating problems such as increased corrosion and overheating due to increased contact resistance. Moreover, the plating layer's abrasion resistance is poor; during terminal insertion and removal, the plating wears away quickly. The worn plating layer's protective performance is reduced, failing to effectively protect the terminal and making it more susceptible to overheating, poor contact, and corrosion, further shortening its service life.

[0007] In view of the above-mentioned related technologies, the inventors believe that it is necessary to improve the existing terminal barrel plating process to improve the uniformity, bonding performance, wear resistance and corrosion resistance of the terminal plating layer, and improve the conductivity of the terminal. Summary of the Invention

[0008] To address the technical deficiencies of existing technologies, this application provides a high-power socket pin core terminal and its barrel plating process.

[0009] In a first aspect, this application provides a barrel plating process for high-power socket pin terminals, employing the following technical solution: A barrel plating process for high-power socket pin terminals includes the following steps: (1) Pre-treat the needle core terminal, the pre-treatment including degreasing, pickling and micro-etching roughening; (2) The pretreated pin core terminal is barrel plated in a pre-plating solution and then barrel plated in a main plating solution to obtain the barrel plated pin core terminal; the pre-plating solution includes a main salt, a complexing agent, a conductive salt and a surfactant; the main plating solution includes a main salt, an organic amine complexing agent, a buffer, a leveling agent, a brightener and modified nano silicon carbide particles. (3) The pin core terminal after barrel plating is subjected to post-plating treatment to obtain the product. The post-plating treatment includes passivation treatment and sealing treatment.

[0010] By adopting the above technical solution, pretreatment removes oil and oxide film from the terminal surface, and micro-etching roughens the surface to form a micro-rough structure, thereby increasing the bonding area with metal particles and improving the adhesion of the plating layer. Further, pre-plating forms a uniform and dense base film on the micro-rough surface, followed by main plating to achieve a uniform and dense plating layer. Modified nano-silicon carbide particles in the main plating solution enhance the wear resistance of the plating layer. Post-plating passivation and sealing treatments enhance corrosion resistance. Through the synergistic effect of these steps, the plating layer is firmly bonded, uniform, wear-resistant, and significantly improves corrosion resistance. Furthermore, the process exhibits high stability, increased production efficiency, and reduced overall cost, meeting environmental protection requirements and effectively extending the terminal's service life.

[0011] Preferably, the degreasing and pickling process includes the following steps: Degreasing: Place the needle core terminal into an alkaline degreasing agent containing sodium hydroxide, sodium carbonate, trisodium phosphate, and octylphenol polyoxyethylene ether-10, and perform ultrasonic degreasing treatment; Pickling: After degreasing, the needle core terminal is rinsed with deionized water, then immersed in a pickling agent containing hydrochloric acid and hexamethylenetetramine at 30-40℃ for 3-5 minutes, and then rinsed with deionized water.

[0012] By adopting the above technical solution, this degreasing and pickling process can effectively improve the surface quality of the pin core terminal. Under ultrasonic action, the alkaline degreasing agent thoroughly removes oil stains through saponification and emulsification reactions; during pickling, hydrochloric acid removes the oxide film, and hexamethylenetetramine prevents over-corrosion, precisely activating the surface and forming a micro-rough structure, providing a good substrate for plating deposition, significantly improving the adhesion and uniformity of the plating, and ensuring the quality of terminal barrel plating.

[0013] Preferably, the micro-etching roughening includes the following steps: Micro-etching and roughening: After pickling, the terminals are placed in a micro-etching agent containing ammonium persulfate and sodium dodecyl sulfate, and reacted at 40-50℃ for 5-8 minutes, and then rinsed with deionized water.

[0014] By adopting the above technical solution, this micro-etching roughening technology uses the synergistic effect of ammonium persulfate and sodium dodecyl sulfate to moderately etch the surface of the pickled terminal at 40-50℃, forming uniform and tiny pits and protrusions within 5-8 minutes, significantly increasing the surface roughness, thereby greatly improving the mechanical bonding ability between the plating layer and the terminal substrate, effectively avoiding the problem of plating layer peeling off during subsequent use, and ensuring the stability of the barrel plating process and the durability of the terminal.

[0015] Preferably, the main salt of the pre-plating solution is potassium gold cyanide, the complexing agent of the pre-plating solution is one of potassium cyanide, sodium potassium tartrate, and sodium thiosulfate; the conductive salt of the pre-plating solution is one of potassium carbonate, sodium sulfate, and potassium nitrate; and the surfactant of the pre-plating solution is one of fatty alcohol polyoxyethylene ether, sodium dodecylbenzene sulfonate, and polyoxyethylene sorbitan fatty acid ester.

[0016] By adopting the above technical solution, potassium gold cyanide, as the main salt, can stably provide gold ions. Different complexing agents can effectively maintain the stability of gold ions in the plating solution and prevent premature reduction. Conductive salts ensure good conductivity of the plating solution, reduce energy consumption, and stabilize current distribution. Surfactants reduce the surface tension of the plating solution, improve wettability, and promote uniform deposition of gold ions. The synergistic effect of the components makes the pre-plating process stable and controllable, forming a thin and dense pre-plating layer, laying a good foundation for subsequent main plating, and improving the adhesion between the plating layer and the terminal substrate and the overall quality.

[0017] Preferably, the organic amine complexing agent in the main plating solution is EDTA, the main salt in the main plating solution is gold sulfite, the buffer in the main plating solution is one of boric acid, citrate, and phosphate, the grain refiner in the main plating solution is one of cerium chloride, sodium hypophosphite, and 2-methylimidazole, the brightener in the main plating solution is one of saccharin, alkynyl alcohols, and pyridine compounds, and the leveling agent in the main plating solution is polyethylene glycol, propynyl alcohol, and pyridine-2-carboxaldehyde.

[0018] By employing the above technical solution, EDTA acts as an organic amine complexing agent to stabilize gold ions, gold sulfite provides the gold ions required for deposition, a buffer maintains the pH stability of the plating bath, a grain refiner refines the plating grains, a brightener enhances the brightness of the plating layer, and a leveling agent improves surface smoothness. The synergistic effect of these components ensures uniform plating deposition during the main plating process, forming a dense, bright, and smooth coating. This significantly improves the adhesion between the plating layer and the substrate, as well as its wear resistance and corrosion resistance, ensuring the stability and reliability of the terminal barrel plating quality.

[0019] Preferably, the method for preparing the modified nano-silicon carbide includes the following steps: The nano-silicon carbide particles are placed in a solution containing silane coupling agent KH-560 and stirred at 300-500 r / min for 1-2 hours at 60-70℃ to form an organic coating layer on the surface of the nano-silicon carbide particles.

[0020] By employing the above technical solution, surface treatment of nano-silicon carbide particles using silane coupling agent KH-560 at 60-70℃, followed by stirring at 300-500 r / min for 1-2 hours, effectively improves the compatibility of nano-silicon carbide with the plating bath, allowing it to disperse uniformly in the main plating bath and preventing agglomeration. During barrel plating, the modified nano-silicon carbide can better embed into the coating, significantly improving the coating's hardness, wear resistance, and scratch resistance, thus enhancing the overall performance of the terminals.

[0021] Preferably, the passivation treatment includes the following steps: The barrel-plated terminals are placed in a passivation solution using trivalent chromium passivating agent at a concentration of 30-50 g / L. The passivation temperature is controlled at 35-45℃, and the passivation time is 8-12 minutes. The passivation process is carried out with intermittent stirring, stirring for 1-2 minutes every 2-3 minutes.

[0022] By employing the above technical solution, at a temperature of 35-45℃, using a trivalent chromium passivating agent with a concentration of 30-50 g / L, combined with a passivation time of 8-12 minutes and intermittent stirring, a uniform and dense passivation film can be formed on the surface of the barrel-plated terminal. This treatment method can effectively isolate external corrosive substances, significantly improve the corrosion resistance of the terminal plating, and ensure the stability and reliability of the terminal in complex environments.

[0023] Preferably, the trivalent chromium passivating agent is one of chromium trichloride, chromium sulfate, and chromium acetate.

[0024] By adopting the above technical solution and the trivalent chromium passivating agent selection scheme, using chromium trichloride, chromium sulfate, or chromium acetate as the passivating agent, a robust passivation layer can be generated on the terminal surface under environmental protection requirements, utilizing the stable chemical properties of trivalent chromium. This passivation layer possesses both good corrosion resistance and chemical stability, avoiding the environmental pollution problems caused by hexavalent chromium, while ensuring passivation effect and coating protection performance.

[0025] Preferably, the sealing process includes the following steps: The passivated needle core terminal is placed in a sealing solution, which includes an organosilicon sealant with a concentration of 20-30 g / L. The sealing temperature is controlled at 50-60℃ and the treatment time is 15-20 min. The organosilicon sealant is one of vinyltriethoxysilane and vinyltrimethoxyethoxysilane.

[0026] By employing the above technical solution, treating the passivated terminals with a vinyl-based silicone sealant at a concentration of 20-30 g / L at 50-60℃ for 15-20 minutes can effectively fill the micropores on the coating surface. This operation further prevents the intrusion of external corrosive media, significantly enhances the corrosion resistance and wear resistance of the coating, and substantially improves the service life and performance of the terminals.

[0027] Secondly, this application provides a high-power socket pin terminal, which adopts the following technical solution: A high-power socket pin core terminal is obtained by the above-mentioned high-power socket pin core terminal barrel plating process, wherein the base material of the pin core terminal is one of pure copper, oxygen-free copper or silver-copper alloy.

[0028] By adopting the above technical solutions, the pin core terminal has both excellent conductivity and coating adhesion: pure copper, oxygen-free copper or silver-copper alloy provides a low-resistance conductive substrate, the surface activity is enhanced after multi-step pretreatment, the gold plating layer formed by pre-plating and main plating is uniform and dense with strong adhesion, modified nano silicon carbide improves wear resistance, and post-plating treatment further enhances corrosion resistance, enabling the terminal to work stably in high current environment, extending service life, and meeting the strict safety and reliability requirements of high-power sockets.

[0029] In summary, this application has the following beneficial effects: 1. The coating produced by the barrel plating process of this invention exhibits excellent performance: Through a series of pretreatment processes, such as alkaline degreasing, hydrochloric acid pickling, and micro-etching roughening, impurities on the substrate surface are effectively removed, and surface activity and roughness are increased, resulting in a stronger bond between the coating and the substrate. During pre-plating and main plating, reasonable control of the plating solution composition and process parameters ensures a uniform and dense gold plating layer. Simultaneously, the embedded modified nano-silicon carbide in the coating enhances its hardness and wear resistance, effectively resisting frictional losses caused by frequent plugging and unplugging of high-power sockets, and ensuring the structural stability and performance reliability of the terminals during long-term use.

[0030] 2. The coating obtained by the barrel plating process of this invention has strong corrosion resistance: After plating, a trivalent chromium passivating agent is used for passivation treatment, forming a passivation film on the coating surface, which can effectively isolate external corrosive substances. Then, an organosilicon sealant is applied to fill the pores of the coating, further enhancing corrosion resistance. This combined process enables the terminals to maintain good conductivity in harsh environments such as humidity and salt spray, extending their service life and meeting the high corrosion resistance requirements of high-power sockets.

[0031] 3. The barrel plating process of this invention is environmentally friendly and efficient: Compared with other electroplating processes, barrel plating reduces waste of plating solution and metal, lowers production costs, and aligns with green environmental protection principles. This application uses trivalent chromium passivating agent instead of the traditional hexavalent chromium system, avoiding the emission of highly toxic substances. Simultaneously, the organosilicon sealing agent has a low volatile organic compound content, making it even more environmentally friendly. Furthermore, precise control of the plating solution composition and process parameters ensures uniform plating thickness, high production yield, and improved production efficiency. Detailed Implementation

[0032] The present application will be further described in detail below with reference to the embodiments.

[0033] The raw materials, consumables, and instruments involved in this embodiment are all commercially available products.

[0034] This embodiment provides a terminal barrel plating process, the specific steps of which are as follows: 1. Preparation before plating (1) Equipment inspection and cleaning: Conduct a comprehensive inspection of the barrel plating equipment, including whether the barrels rotate smoothly, whether the conductive devices are working properly, and whether there are any leaks in the plating solution circulation system. At the same time, thoroughly clean the barrels and related equipment parts to remove any impurities and dirt left over from the previous barrel plating, and ensure that the equipment is in good operating condition.

[0035] (2) Plating solution preparation: The plating solution of the present invention includes a pre-plating solution and a main plating solution, and the specific preparation process and parameters of the two are as follows: Pre-plating solution preparation Select a suitable corrosion-resistant mixing tank, and equip it with a high-precision electronic balance, magnetic stirrer, and thermometer. The operating environment must be clean and well-ventilated, and personnel must take appropriate protective measures.

[0036] Add approximately 80% deionized water to the mixing tank, stir at 300 rpm, heat to 35°C, and slowly add potassium cyanide at a concentration of 30-50 g / L, stirring until dissolved, approximately 15-20 minutes. Cool the solution to room temperature, then add potassium gold cyanide at a concentration of 5-10 g / L, stirring at 400 rpm for 20-30 minutes until dissolved. Next, add potassium carbonate at a concentration of 20-30 g / L, stirring at 400 rpm for 15-20 minutes until dissolved. Finally, add fatty alcohol polyoxyethylene ether at a concentration of 0.5-1 g / L, stirring at 600 rpm for 20 minutes.

[0037] Potassium gold cyanide is the main salt, potassium cyanide is the complexing agent, potassium carbonate is the conductive salt, and fatty alcohol polyoxyethylene ether is the surfactant.

[0038] Other complexing agents include potassium sodium tartrate and sodium thiosulfate.

[0039] Sodium sulfate and potassium nitrate can also be used as conductive salts.

[0040] Surfactants can also be sodium dodecylbenzene sulfonate and polyoxyethylene sorbitan fatty acid ester.

[0041] Main plating solution preparation The same equipment should be prepared for the pre-plating solution, the environment should be clean and dry, and personnel should take protective measures.

[0042] Add approximately 70% deionized water to the mixing tank, stir at 350 rpm, heat to 45°C, and weigh 40-60 g / L of ethylenediaminetetraacetic acid (EDTA), stirring for 20-30 min until dissolved. Cool the solution to room temperature, and weigh 20-30 g / L of gold sulfite, stirring at 400 rpm for 30 min until dissolved. Weigh 30-40 g / L of boric acid, stirring at 400 rpm for 20-30 min until dissolved.

[0043] Surface modification of nanoscale silicon carbide particles was performed. The nanoscale silicon carbide particles were placed in a solution containing the silane coupling agent KH-560 and stirred at 300-500 rpm for 1-2 hours at 60-70℃ to form an organic coating layer on the surface of the nanoscale silicon carbide particles, improving their compatibility with the plating solution. Then, the modified nanoscale silicon carbide particles were added to the plating solution using a combination of high-speed stirring and ultrasonic dispersion. First, the particles were stirred at a high-speed stirring speed of 1000-1500 rpm for 30-60 minutes, followed by ultrasonic dispersion for 20-30 minutes, ensuring uniform dispersion of the nanoscale silicon carbide particles in the plating solution to a concentration of 3-5 g / L. Then, cerium chloride was weighed at 0.05-0.2 g / L and added to the plating solution, and stirred at 500 rpm for 20 minutes. Weigh out saccharin and polyethylene glycol at concentrations of 0.1-0.5 g / L and 0.05-0.2 g / L respectively, add them to the plating solution, and stir at 600 r / min for 20-30 min.

[0044] Among them, EDTA is an organic amine complexing agent, gold sulfite is the main salt, boric acid is a buffer, cerium chloride is a grain refiner, saccharin is a brightener, and polyethylene glycol is a leveling agent.

[0045] Buffers can also be citrates and phosphates, such as trisodium citrate and sodium dihydrogen phosphate.

[0046] Sodium hypophosphite and 2-methylimidazole can also be used as grain refiners.

[0047] Brighteners can also be alkynyl alcohols and pyridine compounds, such as propynyl alcohol and pyridine-2-carboxaldehyde.

[0048] Leveling agents can also be polypropylene glycol or polyethyleneimine.

[0049] (3) Terminal preparation: The socket pin core terminals are cleaned to remove any burrs, flash, or other defects that may exist on the surface. The terminals are then grouped to ensure that each group has a basically consistent size and shape, facilitating unified control of process parameters during subsequent barrel plating. In this embodiment, the pin core terminal substrate is made of pure copper, oxygen-free copper, or a silver-copper alloy.

[0050] 2. Pre-treatment and degreasing of terminal surfaces before barrel plating: The treated terminals are placed in an ultrasonic degreasing tank. The degreasing agent is an alkaline degreasing system formulated with 18 g / L sodium hydroxide, 25 g / L sodium carbonate, 35 g / L trisodium phosphate, and 8 g / L octylphenol polyoxyethylene ether-10 (OP-10) surfactant. The degreasing temperature is controlled at 65±2℃, at which temperature the critical micelle concentration of the surfactant is lowest, and the emulsification efficiency can be increased by 30%; simultaneously, 0.8 W / cm 2Ultrasonic treatment at 40kHz frequency for 12 minutes with high power density utilizes the 50MPa impact pressure generated by the collapse of cavitation bubbles to accelerate oil removal. Compared to traditional immersion degreasing, ultrasonic degreasing can more thoroughly remove oil from the terminal surface, especially oil in some tiny crevices and holes, creating favorable conditions for subsequent plating solution wetting and coating adhesion.

[0051] Pickling and Activation: After degreasing, the terminals are rinsed thoroughly with deionized water and then placed in a pickling tank containing 15-20% (volume fraction) hydrochloric acid solution, with 0.5-1 g / L of hexamethylenetetramine (HOP) added. The pickling temperature is maintained at 30-40℃, and the time is controlled at 3-5 minutes. During the pickling process, the acid reacts chemically with the oxide film on the terminal surface, dissolving and removing it. Simultaneously, the terminal surface is microscopically roughened, increasing active sites and improving the adhesion between the subsequent plating layer and the substrate. After pickling, the terminals are rinsed again with plenty of deionized water to ensure no residual acid remains on the surface. This step optimizes the problem of precise control over the degree of corrosion in traditional pickling processes, ensuring surface activation without affecting the substrate properties of the terminals.

[0052] Micro-etching roughening: To further improve the adhesion between the plating layer and the substrate, micro-etching roughening treatment is performed. The acid-washed terminals are immersed in a micro-etching roughening tank. The main components of the micro-etching solution in the tank include 50-80 g / L of ammonium persulfate and 2-5 g / L of sodium dodecyl sulfate as an accelerator. At 40-50℃, the terminals react with the micro-etching solution for 5-8 minutes. The micro-etching agent undergoes a slight corrosion reaction with the terminal surface, forming uniform, tiny pits and protrusions, significantly increasing surface roughness and thus significantly improving the mechanical adhesion between the plating layer and the substrate. After the reaction is complete, the terminals are rinsed thoroughly with deionized water to provide an ideal surface condition for subsequent barrel plating. This step overcomes the shortcomings of traditional pretreatment processes in improving adhesion, allowing the plating layer to adhere more firmly to the terminal surface during subsequent use.

[0053] (3) Pre-plating process in barrel plating: The pre-treated high-power socket terminals are placed in the pre-plating solution. The pre-plating temperature is controlled at 40-45℃, which ensures the activity of the components in the plating solution and facilitates the uniform deposition of gold ions. The barrel speed is set to 8-12 r / min, allowing the terminals to slowly tumble in the plating solution and ensuring that all parts are in full contact with the plating solution. The current density is set to 0.1-0.2 A / dm³. 2 A lower current density helps to form uniform, fine crystal nuclei. The pre-plating time is 5-10 minutes, forming a thin and uniform pre-plating layer on the terminal surface with a thickness of about 0.5-1 μm.

[0054] Main plating process: After the pre-plating process is successfully completed, carefully remove the terminals from the pre-plating solution and rinse them immediately with pure deionized water. The rinsing process must ensure that any residual pre-plating solution on the terminal surface is completely removed to prevent it from mixing into the main plating solution and affecting the main plating effect. After rinsing, quickly place the terminals into the main plating bath. Maintain the main plating temperature at 50-55℃. Higher temperatures accelerate the deposition rate of gold ions and also facilitate better embedding of nanoparticles in the plating layer. Adjust the roller speed to 15-20 r / min to ensure more thorough tumbling of the terminals and guarantee uniform plating thickness. Set the current density to 0.3-0.5 A / dm³. 2 To ensure coating quality, the deposition rate is increased. The main plating time depends on the desired coating thickness, generally 20-30 minutes, which can achieve a coating thickness of 3-5 μm. During the main plating process, the plating solution is continuously stirred to ensure uniform dispersion of nanoparticles and consistency of the plating solution composition.

[0055] (4) Post-plating treatment After the terminals have completed pre-plating and main plating, post-plating treatment is required to improve corrosion resistance and wear resistance. The specific procedures are as follows: After barrel plating is completed, the plating solution inside the barrel is first drained back into the plating solution storage tank. Then, a large amount of flowing deionized water is injected into the barrel to rinse the terminals. The rinsing time lasts for 5-8 minutes to ensure that any residual plating solution on the terminal surface is completely removed, preventing residual plating solution from adversely affecting subsequent processing and plating quality.

[0056] After rinsing, place the terminals into a passivation solution bath. The passivation solution uses trivalent chromium passivating agent at a concentration of 30-50 g / L. The passivation temperature is controlled at 35-45℃, and the passivation time is 8-12 minutes. During the passivation process, intermittent stirring is used, stirring for 1-2 minutes every 2-3 minutes to ensure the passivation solution fully reacts with the coating surface, forming a uniform and dense passivation film on the coating surface, further improving the corrosion resistance of the coating. After passivation, rinse the terminals with deionized water to remove any residual passivation solution from the surface.

[0057] Trivalent chromium passivating agents can be inorganic acid salts and organic acid salts, such as chromium trichloride, chromium sulfate, and chromium acetate.

[0058] The passivated terminals are then immersed in a sealing solution bath for sealing. The sealing solution mainly consists of an organosilicon sealant at a concentration of 20-30 g / L. The sealing temperature is controlled at 50-60℃, and the treatment time is 15-20 minutes. The sealing solution fills the tiny pores on the coating surface, preventing the intrusion of external corrosive substances and significantly improving the corrosion resistance and wear resistance of the coating. After the sealing treatment, the terminals are rinsed thoroughly with deionized water.

[0059] Organosilicon sealants can be vinyltriethoxysilane or vinyltrimethoxyethoxysilane.

[0060] The sealed terminals are placed in a vacuum drying oven for drying. The drying temperature is set to 80-100℃, the vacuum degree is maintained at 0.08-0.1MPa, and the drying time is 30-40 minutes. Vacuum drying can avoid oxidation or corrosion caused by residual moisture during the drying process, ensuring that the terminal surface is dry and clean, resulting in a high-quality high-power socket pin core terminal product.

[0061] Example 1 Pre-plating preparation Equipment inspection and cleaning: Conduct a comprehensive inspection and cleaning of the barrel plating equipment according to the standard procedures.

[0062] Plating solution preparation Pre-plating solution preparation: Select a corrosion-resistant mixing tank and equip it with appropriate equipment. Add 80% deionized water to the tank, stir at 300 rpm, heat to 35°C, add potassium cyanide at a concentration of 30 g / L, and stir for 15 min until dissolved. After cooling to room temperature, add potassium gold cyanide at a concentration of 5 g / L, and stir at 400 rpm for 20 min until dissolved. Then add potassium carbonate at a concentration of 20 g / L, and stir at 400 rpm for 15 min until dissolved. Finally, add fatty alcohol polyoxyethylene ether at a concentration of 0.5 g / L, and stir at 600 rpm for 20 min.

[0063] Preparation of the main plating solution: Prepare the equipment and environment. Add 70% deionized water to the mixing tank, stir at 350 rpm, heat to 45°C, and weigh 40 g / L of EDTA, stirring for 20 min until dissolved. Cool to room temperature, weigh 20 g / L of gold sulfite, and stir at 400 rpm for 30 min until dissolved. Weigh 30 g / L of boric acid, and stir at 400 rpm for 20 min until dissolved. Surface-modify the nano-silicon carbide particles with silane coupling agent KH-560 at 60°C and 300 rpm for 1 h, then stir at 1000 rpm for 30 min, followed by ultrasonic dispersion for 20 min before adding to the plating solution to achieve a concentration of 3 g / L. Weigh 0.05 g / L of cerium chloride, stir at 500 rpm for 20 min, and add to the plating solution. Weigh out saccharin and polyethylene glycol at concentrations of 0.1 g / L and 0.05 g / L respectively, and add them to the plating solution while stirring at 600 rpm for 20 minutes.

[0064] Terminal preparation: Select pure copper pin core terminals and clean and remove burrs and flash.

[0065] Pre-treatment and degreasing of terminal surfaces before barrel plating: At 63°C, an alkaline degreasing system containing 18 g / L sodium hydroxide, 25 g / L sodium carbonate, 35 g / L trisodium phosphate, and 8 g / L LOP-10 surfactant is used at a concentration of 0.8 W / cm². 2 Ultrasonic treatment at power density and 40kHz frequency for 12 minutes.

[0066] Pickling activation: Pickle for 3 minutes at 30°C with an acid solution containing 15% (volume fraction) hydrochloric acid and 0.5 g / L of corrosion inhibitor hexamethylenetetramine.

[0067] Micro-etching roughening: At 40℃, treat with a micro-etching solution containing 50 g / L ammonium persulfate and 2 g / L sodium dodecyl sulfate for 5 min.

[0068] Pre-plating process in barrel plating: At 40℃, with a barrel speed of 8 r / min and a speed of 0.1 A / dm 2 Pre-plating at the current density for 5 minutes.

[0069] Main plating process: After pre-plating, rinse thoroughly and immerse in the main plating solution. At 50℃, with a drum speed of 15 r / min and an A / dm² spray rate, the plating is carried out at a speed of 0.3 A / dm². 2 The current density was used for the main plating for 20 minutes.

[0070] Post-plating treatment Rinse with deionized water for 5 min, then passivate with 30 g / L chromium trichloride at 35 °C for 8 min with intermittent stirring. After passivation, seal with 20 g / L vinyltriethoxysilane at 50 °C for 15 min. After sealing, dry at 80 °C and 0.08 MPa vacuum for 30 min.

[0071] Example 2 Pre-plating preparation Equipment inspection and cleaning: Same as in Example 1.

[0072] Plating solution preparation Pre-plating solution preparation: The operation is the same as in Example 1, except that potassium cyanide is weighed at 50 g / L, potassium gold cyanide at 10 g / L, potassium carbonate at 30 g / L, and fatty alcohol polyoxyethylene ether at 1 g / L.

[0073] Preparation of main plating solution: The operation is the same as in Example 1, except that EDTA is weighed at 60 g / L, gold sulfite at 30 g / L, boric acid at 40 g / L, nano silicon carbide particles at 5 g / L, cerium chloride at 0.2 g / L, saccharin at 0.5 g / L, and polyethylene glycol at 0.2 g / L.

[0074] Terminal preparation: Select oxygen-free copper needle core terminals, clean and remove burrs and flash before grouping.

[0075] Pre-treatment and degreasing of terminal surfaces before barrel plating: At 67°C, an alkaline degreasing system containing 18 g / L sodium hydroxide, 25 g / L sodium carbonate, 35 g / L trisodium phosphate, and 8 g / L LOP-10 surfactant is used at a concentration of 0.8 W / cm². 2 Ultrasonic treatment at power density and 40kHz frequency for 12 minutes.

[0076] Pickling activation: Pickle for 5 minutes at 40°C with an acid solution containing 20% ​​(volume fraction) hydrochloric acid and 1 g / L of corrosion inhibitor hexamethylenetetramine.

[0077] Micro-etching roughening: At 50°C, treat with a micro-etching solution containing 80 g / L ammonium persulfate and 5 g / L sodium dodecyl sulfate for 8 min.

[0078] Barrel plating process Pre-plating process: At 45℃, with a drum speed of 12r / min and an A / dm² temperature... 2 Pre-plating at the current density for 10 minutes.

[0079] Main plating process: After pre-plating, rinse thoroughly and immerse in the main plating solution. At 55℃, with a drum speed of 20 r / min and an A / dm² spray rate, plating is performed. 2 The current density was used for the main plating for 30 minutes.

[0080] Post-plating treatment Rinse with deionized water for 8 min to remove plating solution. After rinsing, passivate with 50 g / L chromium sulfate at 45°C for 12 min with intermittent stirring. After passivation, seal with 30 g / L vinyltrimethoxyethoxysilane at 60°C for 20 min. After sealing, dry at 100°C and 0.1 MPa vacuum for 40 min.

[0081] Example 3 Pre-plating preparation Equipment inspection and cleaning: Same as in Example 1.

[0082] Plating solution preparation Pre-plating solution preparation: Sodium potassium tartrate is selected as the complexing agent, weighed at 60 g / L. Other operations are the same as in Example 1, but potassium carbonate is replaced with sodium sulfate, weighed at 70 g / L. Sodium dodecylbenzene sulfonate is selected as the surfactant, weighed at 0.6 g / L.

[0083] Main plating solution preparation: Citrate (trisodium citrate) is selected as the buffer, weighed at 20 g / L. Other operations are the same as in Example 1, but the grain refiner is sodium hypophosphite, weighed at 0.3 g / L, the brightener is propynyl alcohol, weighed at 0.15 g / L, and the leveling agent is polypropylene glycol, weighed at 0.1 g / L.

[0084] Terminal preparation: Select silver-copper alloy pin core terminals, clean and remove burrs and flash before grouping.

[0085] Pre-treatment and degreasing of terminal surfaces before barrel plating: At 65°C, an alkaline degreasing system containing 18 g / L sodium hydroxide, 25 g / L sodium carbonate, 35 g / L trisodium phosphate, and 8 g / L LOP-10 surfactant is used at a concentration of 0.8 W / cm². 2 Ultrasonic treatment at power density and 40kHz frequency for 12 minutes.

[0086] Pickling activation: Pickle for 4 minutes at 35°C with an acid solution containing 18% (volume fraction) hydrochloric acid and 0.8 g / L of corrosion inhibitor hexamethylenetetramine.

[0087] Micro-etching roughening: At 45°C, the sample was treated with a micro-etching solution containing 65 g / L ammonium persulfate and 3.5 g / L sodium dodecyl sulfate for 6.5 min.

[0088] Pre-plating process in barrel plating: At 42.5℃, with a barrel speed of 10 r / min and an A / dm² of 0.15A. 2 Pre-plating at a current density of 7.5 min.

[0089] Main plating process: After pre-plating, rinse thoroughly and immerse in the main plating solution. Plating is carried out at 52.5℃ with a drum speed of 17.5 r / min and an A / dm³ / dt. 2 The current density was used for the main plating for 25 minutes.

[0090] Post-plating treatment: Rinse with deionized water for 6 min to remove plating solution. After rinsing, passivate with 40 g / L chromium acetate at 40℃ for 10 min with intermittent stirring. After passivation, seal with 25 g / L vinyltrimethoxyethoxysilane at 55℃ for 20 min. After sealing, dry at 90℃ and 0.09 MPa vacuum for 35 min.

[0091] To further verify the performance of the barrel plating process of the present invention, comparative examples 1-4 were set up based on Example 1.

[0092] Comparative Example 1 The barrel plating process in this comparative example is basically the same as that in Example 1. The difference is that the pretreatment of the terminal surface before barrel plating in this comparative example does not include micro-etching roughening treatment.

[0093] Comparative Example 2 The barrel plating process in this comparative example is basically the same as that in Example 1. The difference is that this comparative example only prepares the main plating solution and only performs the main plating during the barrel plating process.

[0094] Comparative Example 3 The barrel plating process in this comparative example is basically the same as that in Example 1. The difference is that the pretreatment of the terminal surface before barrel plating in this comparative example does not include micro-etching roughening treatment. This comparative example only prepares the main plating solution and only performs the main plating during the barrel plating process.

[0095] Comparative Example 4 The barrel plating process in this comparative example is basically the same as that in Example 1. The difference is that the main plating solution in this comparative example does not contain grain refiners and modified nano-silicon carbide.

[0096] To further verify the comparison between the barrel plating process of the present invention and the prior art, a prior art comparative example 5 is set up.

[0097] Comparative Example 5 Equipment inspection and cleaning: A simple inspection of the barrel plating equipment is performed to ensure that the drums can rotate and that the conductive devices are not obviously damaged. However, the equipment will not be deeply cleaned; only large, obvious impurities will be removed.

[0098] Plating solution preparation: A single plating solution is used for barrel plating, without distinguishing between pre-plating solution and main plating solution. The main component of the plating solution is a traditional cyanide gold plating solution, with a potassium gold cyanide concentration of 40 g / L, potassium cyanide as a complexing agent at a concentration of 120 g / L, and the addition of brightener saccharin and leveling agent polyethylene glycol.

[0099] Terminal preparation: The terminals are basically the same as in Example 1, except that the base material of the pin core terminal is ordinary copper.

[0100] Pre-treatment of terminal surfaces before barrel plating: Degreasing treatment. Place the terminals in a common alkaline degreasing tank. The degreasing agent is a mixed solution of sodium hydroxide and sodium carbonate, with sodium hydroxide at 20-30 g / L and sodium carbonate at 30-40 g / L. Immerse at room temperature for 20-30 minutes. Do not use ultrasonic assistance; remove oil stains solely through the chemical reaction between the solution and the oil, and through simple immersion.

[0101] Pickling and activation: Immerse the degreased terminals in a hydrochloric acid solution with a concentration of approximately 10-15% (volume fraction) at 25-35°C for 5-10 minutes.

[0102] Barrel plating process The pretreated terminals were directly immersed in the plating solution, which was maintained at 50-55℃. The drum speed was fixed at 20 r / min, and the current density was set to 0.6 A / dm³. 2 The electroplating time is set to 30-40 minutes based on experience.

[0103] Post-plating treatment After electroplating, the terminals were simply rinsed with water for 5 minutes, and then passivated with chromium trichloride passivating agent at a concentration of 30 g / L and a temperature of 40°C for 15 minutes. The passivated terminals were then dried in a regular oven at a temperature of 90°C for 20 minutes.

[0104] The size and dimensions of the pin core terminals used in the above embodiments and the comparative barrel plating process are all the same.

[0105] Performance testing The pin core terminals prepared by the barrel plating process in Examples 1-3 and Comparative Examples 1-5 were used as samples for performance testing.

[0106] The corrosion test of metals and alloys by salt solution was carried out in a simulated humid atmospheric environment according to the standard GB / T19746-2018. The test solution contained an aqueous solution of 1 g / L acetic acid and 1 g / L sodium chloride. After 3 weeks of immersion, the corrosion depth of the sample was tested, the corrosion rate was calculated, and the corrosion of the sample was observed and recorded. The results are recorded in Table 1.

[0107] The results are divided into 1-5 levels, and the specific result criteria are as follows: Level 1: The average corrosion depth is less than 0.05 mm, indicating that the corrosion of the metal under the test conditions is very slight, with minimal impact on the thickness of the material and no impact on its key properties such as structural strength and dimensional accuracy.

[0108] Level 2: The average corrosion depth is between 0.05mm and 0.15mm. The metal has a certain degree of corrosion, but the corrosion depth is still within a relatively safe range. In some applications that are not very sensitive to changes in material thickness, it may not cause serious consequences.

[0109] Level 3: The average corrosion depth is between 0.15mm and 0.3mm. Further increases in corrosion depth may have a certain impact on the mechanical properties and dimensional accuracy of the material. The degree of impact on product performance needs to be assessed based on the specific circumstances.

[0110] Level 4: The average corrosion depth is between 0.3mm and 0.5mm. The metal is severely corroded, and the corrosion depth is large. This may significantly affect the structural strength and service life of the material, and in many cases, it no longer meets the usage standards.

[0111] Level 5: The average corrosion depth is greater than 0.5 mm. The metal is severely corroded, the corrosion depth is too large, and the structure of the material may have been severely damaged, making it impossible to continue normal use.

[0112] According to the "Standard for Bond Strength of Metal Coatings for Light Industrial Products" (QB / T3821-1999), the bonding strength of the coating was tested using a cross-cut test. A hard steel knife with a blade sharpened to a 30° acute angle was used to cut a 1mm × 1mm grid on the sample surface. Sufficient pressure was applied during the cutting process so that the knife could cut through the coating and reach the base metal in one stroke. A piece of transparent adhesive tape with an adhesion strength of 2–3.5 N / cm² was then applied to the cut surface of the coating with a finger, left for 10 seconds, and then applied pressure perpendicular to the coating surface before quickly peeling off the tape. Each sample was tested three times, and the results are recorded in Table 1.

[0113] The results are divided into 1-5 levels, and the specific criteria for the results are as follows: Level 1: The coating within the cut grid is completely intact. After the tape is peeled off, the grid lines are clear, and the coating is tightly bonded to the substrate. Under the stress applied in the cross-cut test, the adhesion between the coating and the substrate is sufficient to resist the tensile force generated by the tape peeling, indicating that the coating bonding strength is extremely high.

[0114] Level 2: The area of ​​coating peeling off within the grid area does not exceed 5%. Only a very small amount of coating is lifted when the tape is peeled off, indicating that the coating has a strong bond with the substrate. Although there is slight coating peeling, the overall bonding is still very good.

[0115] Level 3: The area of ​​coating peeling off within the grid area is between 5% and 15%. At this point, the coating peeling is quite obvious, but still within an acceptable range, indicating that the coating has good adhesion to the substrate. However, under some harsh usage conditions, such as frequent friction or large external impacts, there is a risk that the coating may peel off further.

[0116] Level 4: The area of ​​coating peeling off within the grid area is between 15% and 35%. A large area of ​​coating peeling off indicates that the adhesion between the coating and the substrate is relatively weak. During the use of the product, the coating may gradually peel off, affecting the product's appearance and protective performance. This level may be suitable for some light industrial products where the requirements for coating adhesion are not particularly high and the use environment is relatively mild, such as some temporary or disposable metal packaging materials.

[0117] Level 5: The area of ​​coating peeling off within the grid region exceeds 35%. Extensive coating peeling indicates extremely poor adhesion between the coating and the substrate. Such a coating cannot provide effective protection and decoration for the product, failing to meet the basic quality requirements for coating adhesion in light industrial products. During normal use, the coating is likely to peel off over a large area, severely impacting product quality.

[0118] The wear resistance test was conducted using the standard "QB / T3820-1999 Abrasion Resistance Test of Metal Coatings and Chemical Treatment Layers of Light Industrial Products". The test pressure was 5N, the friction material was a rubber wheel containing diamond grit, the number of friction cycles was 100, and the wear results were recorded in Table 1.

[0119] In addition, observe the metal parts after barrel plating to see if the plating layer is uniform and fine, and whether there are any phenomena such as expansion or peeling. The results are recorded in Table 1.

[0120] Table 1 Performance Test Results As shown in Table 1, the pin terminals of Examples 1-3 using the barrel plating process of this invention exhibit excellent performance in various tests. In the immersion test, the corrosion rate all reached Level 1, with a corrosion rate of 0.001 mm / a. This means that under simulated humid atmospheric conditions, the pin terminals prepared by the process of this invention demonstrate extremely strong corrosion resistance, with minimal impact on material thickness and almost no damage to key properties such as structural strength and dimensional accuracy. In the coating bonding strength test, all also reached Level 1, with no coating peeling off within the cut grid, indicating a tight bond between the coating and the substrate, possessing extremely high bonding strength, effectively resisting external forces, and ensuring the stability of the coating in various usage scenarios. The wear resistance test results were also excellent, with the wear amount per wear cycle less than 0.3 mg, such as 0.26 mg / cycle in Example 1, 0.27 mg / cycle in Example 2, and 0.24 mg / cycle in Example 3, fully demonstrating the excellent wear resistance of the pin terminals prepared by the barrel plating process of this invention. Furthermore, the coatings appear uniform and fine, without any defects such as expansion or peeling, further verifying the reliability of this process in improving product quality.

[0121] Comparing the data of Example 1 with those of Comparative Examples 1-4, it is evident that the corrosion resistance, adhesion to the substrate, wear resistance, and uniformity of the coating in Example 1 are superior to those in Comparative Examples 1-4. This indicates that the core steps in the barrel plating process of this invention, such as micro-etching and roughening, double-layer electroplating, and improved plating solution, are indispensable. Furthermore, the data for Comparative Example 5 (prior technology) are significantly inferior to those of Example 1. Therefore, it is clear that the barrel plating process of this invention can significantly improve the corrosion resistance, adhesion to the substrate, wear resistance, and uniformity of the coating compared to prior art.

[0122] In addition, the substrate of the pin core terminal of the present invention is made of pure copper, oxygen-free copper or silver-copper alloy, combined with a full gold plating, which has excellent conductivity. At the same time, the substrate and plating have high heat dissipation coefficients and also have good heat dissipation performance.

[0123] In summary, through detailed data analysis of various embodiments and comparative examples, it can be seen that the barrel plating process of the present invention has significant advantages in improving the corrosion resistance, coating bonding strength and wear resistance of the pin core terminal. Each key step and component plays an indispensable role in ensuring product quality and performance.

[0124] This specific embodiment is merely an explanation of this application and is not intended to limit it. After reading this specification, those skilled in the art can make modifications to this embodiment without contributing any inventive step, but such modifications are protected by patent law as long as they fall within the scope of the claims of this application.

Claims

1. A barrel plating process for high-power socket pin core terminals, characterized in that, Includes the following steps: (1) Pre-treat the needle core terminal, the pre-treatment including degreasing, pickling and micro-etching roughening; (2) The pretreated pin core terminal is barrel plated in a pre-plating solution and then barrel plated in a main plating solution to obtain the barrel plated pin core terminal; the pre-plating solution includes a main salt, a complexing agent, a conductive salt and a surfactant; the main plating solution includes a main salt, an organic amine complexing agent, a buffer, a leveling agent, a brightener and modified nano silicon carbide particles. (3) The pin core terminal after barrel plating is subjected to post-plating treatment to obtain the product. The post-plating treatment includes passivation treatment and sealing treatment.

2. The barrel plating process for high-power socket pin terminals according to claim 1, characterized in that: The degreasing and pickling process includes the following steps: Degreasing: Place the needle core terminal into an alkaline degreasing agent containing sodium hydroxide, sodium carbonate, trisodium phosphate, and octylphenol polyoxyethylene ether-10, and perform ultrasonic degreasing treatment; Pickling: After degreasing, the needle core terminal is rinsed with deionized water, then immersed in a pickling agent containing hydrochloric acid and hexamethylenetetramine at 30-40℃ for 3-5 minutes, and then rinsed with deionized water.

3. The barrel plating process for high-power socket pin terminals according to claim 1, characterized in that: The micro-etching roughening includes the following steps: Micro-etching and roughening: After pickling, the terminals are placed in a micro-etching agent containing ammonium persulfate and sodium dodecyl sulfate, and reacted at 40-50℃ for 5-8 minutes, and then rinsed with deionized water.

4. The barrel plating process for high-power socket pin terminals according to claim 1, characterized in that: The main salt of the pre-plating solution is potassium gold cyanide, and the complexing agent of the pre-plating solution is one of potassium cyanide, sodium potassium tartrate, and sodium thiosulfate; the conductive salt of the pre-plating solution is one of potassium carbonate, sodium sulfate, and potassium nitrate, and the surfactant of the pre-plating solution is one of fatty alcohol polyoxyethylene ether, sodium dodecylbenzene sulfonate, and polyoxyethylene sorbitan fatty acid ester.

5. The barrel plating process for a high-power socket pin core terminal according to claim 4, characterized in that: The organic amine complexing agent in the main plating solution is EDTA; the main salt in the main plating solution is gold sulfite; the buffer in the main plating solution is one of boric acid, citrate, and phosphate; the grain refiner in the main plating solution is one of cerium chloride, sodium hypophosphite, and 2-methylimidazole; the brightener in the main plating solution is one of saccharin, alkynyl alcohols, and pyridine compounds; and the leveling agent in the main plating solution is polyethylene glycol, propynyl alcohol, and pyridine-2-carboxaldehyde.

6. The barrel plating process for a high-power socket pin core terminal according to claim 5, characterized in that: The method for preparing the modified nano-silicon carbide includes the following steps: The nano-silicon carbide particles are placed in a solution containing silane coupling agent KH-560 and stirred at 300-500 r / min for 1-2 hours at 60-70℃ to form an organic coating layer on the surface of the nano-silicon carbide particles.

7. The barrel plating process for a high-power socket pin core terminal according to claim 1, characterized in that: The passivation process includes the following steps: The barrel-plated terminals are placed in a passivation solution using trivalent chromium passivating agent at a concentration of 30-50 g / L. The passivation temperature is controlled at 35-45℃, and the passivation time is 8-12 minutes. The passivation process is carried out with intermittent stirring, stirring for 1-2 minutes every 2-3 minutes.

8. The barrel plating process for a high-power socket pin core terminal according to claim 7, characterized in that: The trivalent chromium passivating agent is one of chromium trichloride, chromium sulfate, and chromium acetate. According to claim 1, the barrel plating process for a high-power socket pin core terminal is characterized in that the sealing treatment includes the following steps: The passivated needle core terminal is placed in a sealing solution, which includes an organosilicon sealant with a concentration of 20-30 g / L. The sealing temperature is controlled at 50-60℃ and the treatment time is 15-20 min. The organosilicon sealant is one of vinyltriethoxysilane and vinyltrimethoxyethoxysilane.

9. A high-power socket pin terminal, characterized in that: The high-power socket pin core terminal is produced by a barrel plating process according to any one of claims 1-9, wherein the substrate of the pin core terminal is one of pure copper, oxygen-free copper, or silver-copper alloy.